A multi-featured shape memory alloy constitutive model incorporating tension–compression asymmetric interpolation. (September 2022) - Woodworth, Lucas A.; Wang, Xiaonan; Lin, Guoyu; Kaliske, Michael
Abstract: The mechanical response of shape memory alloys is heavily governed by phase transformation and plasticity. These inelastic mechanisms present added complexities in the form of asymmetries with respect to the stress state (tension–compression asymmetry) and the direction (forward or reverse) of transformation, leading to the formation of internal loops. With this in mind, a constitutive model is developed incorporating phase transformation and yield plasticity. The model represents the tension–compression asymmetry through a novel approach by interpolating the maximum transformation strain, the Young's modulus of martensite and a plasticity factor in the deviatoric plane of the transformation strain direction. Internal loops are also considered by scaling the transformation hardening and the hysteresis width based on memory points. The interaction between the processes of reorientation and phase transformation is also taken into account. The model is validated with several proportional and non-proportional loading tests with considerable success. The capability of the model to simulate complex loading scenarios is demonstrated by simulating the manufacturing and loading of a stent structure. Highlights: tension–compression asymmetry of transformation and plasticity accounted for. Novel interpolation method employed for the tension–compression asymmetry. Internal loops modeled with changes in hardening and hysteresis width. Modified radial return mapping applied for the yield plasticity. Simulation of the manufacturing and loading of a stent structure.